Effects of concentration of Follicle Stimulating Hormone (FSH) on the rates of ovulations and twinning birth - Situmorang, Polmer; Sianturi, R; Kusumaningrum, D. A; Triwulaningsih, E (Indonesian Animal Sciences Society, 2010)
Twinning in monotocous domestic species dairy cattle is most frequently by dyzygote in which two eggs is ovulated by treatment with gonadotropin hormon. A study to see the effects of concentration of Follicle Stimulating Hormone (Folltropin) on the ovulation rates and twinning birth was conducted. The experiment designed was commpletely randomized designed with 3 treatment of total concentration of FSH (A: 12, B: 6 and C 3 ml) and 4 lactating cows for a replications. Hormon was intramussculary injected in decreasing dossis method twice a day with 12 hours apart for 4 days. Data recorded were the diameter of ovary (DO), total corpus luteum (TCL), concentration of progesterone on the day 12 of estrus cycle (P), percentage of pregnancy and number of birth. FSH significantly increased the ovulation rates. The means DO was significantly (P < 0.05) higher after injection (6.3 cm) than those before injection (2.0 cm). The TCL and P were highly significant (P < 0.01) higher after injection. The TCL and P were 1.2 and 0.8 ng/ml and 8.5 and 3.0 ng/ml before and after hormone treatment respectively. Concentration of FSH significantly increase (P < 0.05) the TCL and P but not for DO. The means DO, TCL and P were 5.0, 4.5 and 1.6, 5.5, 8,8 and 1.8 and 8.4cm, 12.3 and 5.3 ng/ml for treatments C, B and A respectively. Persentage of pregnancy was decreasing by the increasing of ovulations rates and the highest percentage of pregnancy 75% was obtained on treatments C. The normal single birth was found for treatment C and neonatal death were occurred for treatment B and A where the number of calves is higher than 2. In conclusion the FSH increased the ovulation rates in dairy cattle and the ovulation rates obtained was also affected by the concentration of hormone. Key Words: Hormone, FSH, Ovulation, Twin Birth